Antimalarial drug quality: methods to detect suspect drugs. Issue 1 (January 2010) - Kaur, Harparkash; Green, Michael D; Hostetler, Dana M; Fernáández, Facundo M; Newton, Paul N
Malaria is a major public health problem in the endemic countries of Africa, Asia and Latin America. Poor quality antimalarials are of major, but neglected, concern in the control of Plasmodium falciparum malaria. They cause treatment failure and economic loss, and engender drug resistance and loss of confidence in health systems. The emergence of resistance to the artemisinin derivatives in Asia bodes ill for malaria control in Africa, and strenuous efforts are needed to improve the quality of the world''s supply of antimalarials. This article reviews the problem and discusses methods available to determine the quality of antimalarials.